E-PROCUREMENT DALAM MENCEGAH TINDAK FRAUD (Studi Kasus pada Satker X Pemerintah Pusat) - Nerissa, Paxia Prima; Hadiprajitno, Paulus Theodorus Basuki (Jurnal Ilmu Manajemen dan Akuntansi Terapan (JIMAT), 2022)
This study discusses the role of e-procurement in preventing fraud in Satker X. This study is devoted to examining the role of e-procurement in preventing fraud, as well as the potential for fraud that may still occur when Satker X has implemented e-procurement in procurement process. The object of this research is Satker X which is one of the Central Government Work Units engaged in the field of vocational education. This research is aimed at Satker X as e-procurement users.Research espondent in this study are 3 respondents. Data collection in this study was done by in-depth interviews, observation and documentation. After the data is collected, the next step is analyze the data. Data were analyzed by data reduction, presented in tabular form, until the stage of completion of writing and drawing conclusions. The validity or credibility test of the data is done by using data triangulation.The results show that the implementation of e-procurement in Satker X is quite good, and e-procurement has been proven to increase transparency and accountability in the procurement process in Satker X. However, it turns out that e-procurement still has gaps that can later become one of the potential fraud in the future. It was found that e-procurement is considered less able to prevent fraud that can occur during the implementation of work. Where there is manipulating documents carried out by unscrupulous provider. To avoid this from happening in the future, it is hoped that Satker X and the bureaucracy above it can always evaluate the implementation of work of the procurement of goods and services, besides that Satker X and the bureaucracy above it must also start building an integrity zone, by increasing the integrity of implementers, starting from KPA, planners, PPK, UKPBJ, and the work supervisor.